2016
DOI: 10.1016/j.nmni.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Possible healthcare-associated transmission as a cause of secondary infection and population structure of Staphylococcus aureus isolates from two wound treatment centres in Ghana

Abstract: We have previously shown that secondary infections of Buruli ulcer wounds were frequently caused by Staphylococcus aureus. To gain understanding into possible routes of secondary infection, we characterized S. aureus isolates from patient lesions and surrounding environments across two Ghanaian health centres. One hundred and one S. aureus isolates were isolated from wounds (n = 93, 92.1%) and the hospital environment (n = 8, 7.9%) and characterized by the spa gene, mecA and the Panton–Valentine leucocidin tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 28 publications
3
31
0
Order By: Relevance
“…The frequency of tetK gene found in this study (19.0%) is close to that reported in another study in Ghana (16.3%) (28).…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of tetK gene found in this study (19.0%) is close to that reported in another study in Ghana (16.3%) (28).…”
Section: Discussionsupporting
confidence: 89%
“…All lesions were culture positive until 2 weeks but thereafter all were culture negative . Some follow‐up studies have indicated that healing delay may occur in up to two‐thirds of patients within 25 weeks from the start of SR treatment . Sarfo et al.…”
Section: Prolong Viability Of Mu In Bu Lesionsmentioning
confidence: 98%
“…Reported practices, including not washing of wounds and surrounding intact skin, removal of old dressings without moistening exposing the wounds to trauma, wounds being cleaned by rubbing cotton wool soaked with dressing solutions on the wound instead of the application of moderate‐pressure irrigation, the choice of using different topical antiseptics instead of normal saline for wound cleaning, frequency of dressing changes not based on wound characteristics but on hospital policy, and the use of unsterilized materials for dressing wounds, have the potential of negatively impacting the healing of patients, increasing the risk of secondary infection of wounds, and ultimately delaying their reintegration into their families and society . The WHO guidelines for wound management exist and reports have shown that health workers have adequate knowledge and training on these guidelines; however, in some health facilities, adherence to the guidelines and delivery of proper wound care is hampered by the lack of adequate infrastructure, equipment, and wound dressing supplies . Providing appropriate facilities and tools to these health centers will empower them to be able to provide good care to patients.…”
Section: Prolong Viability Of Mu In Bu Lesionsmentioning
confidence: 99%
“…Conventional PCR was used for the genetic detection of three major ESBL genes namely; blaTEM, blaSHV and blaCTX-M from the E. coli (11), Klebsiella pneumonia (13) and Pseudomonas aeruginosa (8) isolates obtained in the study. The primers used for each gene have been described in previous studies [33].…”
Section: Polymerase Chain Reaction For Detection Of Esbl Genesmentioning
confidence: 99%
“…The increased interest in the use of copper surfaces in ICUs to reduce surface microbial load is testament of the potential role the environment may play in cross-transmission of HAIs [12]. Furthermore, numerous studies have employed molecular characterisation techniques including whole genome sequencing and Pulsed-field gel Electrophoresis (PFGE) to determine definitive genomic similarities between pathogens isolated from the hospital environment, HCWs hands as well as clinical specimens from admitted patients [7,8,13,14]. It has also been extensively reported that patients admitted into rooms previously occupied by a patient infected by MRSA, Clostridium difficile, Acinetobacter baumannii or vancomycinresistant enterococci (VRE) were more likely to acquire the infection of a previously admitted patient [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%